Assessing the presence of oligoclonal IgM bands as a prognostic biomarker of cognitive decline in the early stages of multiple sclerosis - Clàudia Coll‐Martinez; Ester Quintana; Judit Salavedra‐Pont; Maria Buxó; Marina González‐del‐Rio; Immaculada Gómez; María Muñoz‐San Martín; Luisa María Villar; Gary Álvarez‐Bravo; René Robles‐Cedeño; Lluís Ramió‐Torrentà; Jordi Gich (Brain and Behavior, 2021)
Abstract Background An association has been found between the presence of lipid‐specific oligoclonal IgM bands (LS‐OCMB) in cerebrospinal fluid and a more severe clinical multiple sclerosis course. Objective To investigate lipid‐specific oligoclonal IgM bands as a prognostic biomarker of cognitive impairment in the early stages of multiple sclerosis. Methods Forty‐four patients underwent neuropsychological assessment at baseline and 4 years. Cognitive performance at follow‐up was compared adjusting by age, education, anxiety–depression, and baseline performance. Results LS‐OCMB+ patients only performed worse for Long‐Term Storage in the Selective Reminding Test (p = .018). Conclusion There are no remarkable cognitive differences between LS‐OCMB– and LS‐OCMB+ patients in the early stages of MS.